Incidence and Predictors of Acute Ischemic Lesions on Brain Magnetic Resonance Imaging in Patients With a Clinical Diagnosis of Transient Ischemic Attack in China - Yuan, Junliang; Jia, Zejin; Song, Yangguang; Yang, Shuna; Li, Yue; Yang, Lei; Qin, Wei; Hu, Wenli (Frontiers in Neurology, 2019)
Background: The associations between the clinical characteristics and diffusion- weighted imaging (DWI) positivity in patients with a clinical diagnosis of transient ischemic attack (TIA) are still poorly understood. The purpose of our study was aimed to determine the incidence of TIA related acute infarction by DWI, and to determine the underlying predictors of DWI positivity in TIA patients. Methods: Between Jan 2017 and Dec 2018, we retrospectively enrolled 430 patients with a clinical diagnosis of TIA and underwent DWI. Patients were divided into those with acute ischemic lesions (DWI positive group) and those without (DWI negative group). The clinical characteristics, laboratory data, and imaging parameters were compared between the two groups. Results: A total of 430 time-based TIA patients (mean age, 61.4±13.0) were enrolled in this study. About 126 (29.3%) of TIA patients had a DWI positive lesion in our series. Comparing TIA patients with positive DWI to those negative DWI, acute lesions were more likely to be more male, higher hyperlipidemia and smoking history, more speech abnormalities and motor weakness; and higher systolic and diastolic blood pressure, homocysteine, fasting blood glucose, and the scores of ABCD2, ABCD3, ABCD3-I and Dawson. Several independent predictors of DWI positivity were identified with logistic regression analysis: motor weakness (odds ratio 4.861, P=0.021), speech abnormalities (odds ratio 4.029, P=0.024) and ABCD3-I (odds ratio 13.141, P=0.001). ABCD3-I showed the greatest area under the ROC curve，with a sensitivity of 85.7% and specificity of 72.4%. Conclusion: In patients with a clinical diagnosis of TIA, 29.3% demonstrated acute DWI lesions on brain MRI. They were associated with motor weakness, speech abnormalities and higher ABCD3-I score at admission.